Self-organization of adatom adsorption structure at interaction with tip of dynamic force microscope - Khomenko, A.V. (Condensed Matter Physics, 2014)
The formation of an adatom adsorption structure in dynamic force microscopy experiment is shown as a result of the spontaneous appearance of shear strain caused by external supercritical heating. This transition is described by the Kelvin-Voigt equation for a viscoelastic medium, the relaxation Landau-Khalatnikov equation for shear stress, and the relaxation equation for temperature. It is shown that these equations formally coincide with the synergetic Lorenz system, where the shear strain acts as the order parameter, the conjugate field is reduced to the stress, and the temperature is the control parameter. Within the adiabatic approximation, the steady-state values of these quantities are found. Taking into account the sample shear modulus vs strain dependence, the formation of the adatom adsorption configuration is described as the first-order transition. The critical temperature of the tip linearly increases with the growth of the effective value of the sample shear modulus and decreases with the growth of its typical value. Формування структури адсорбованих адатомiв при дослiдженнi в режимi динамiчної силової мiкроскопiї
представлено як результат спонтанної появи зсувної деформацiї в результатi зовнiшнього надкритичного нагрiвання. Цей перехiд описується рiвнянням Кельвiна-Фойгта для в’язкопружного середовища,
релаксацiйним рiвнянням Ландау-Халатнiкова для зсувних напружень та релаксацiйним рiвнянням для
температури. Показано, що цi рiвняння формально збiгаються iз синергетичною системою Лоренца, де
зсувна деформацiя вiдiграє роль параметра порядку, спряжене поле зводиться до напружень, та температура є керувальним параметром. В рамках адiабатичного наближення знайденi стацiонарнi значення цих
величин. Враховуючи залежнiсть модуля зсуву зразка вiд деформацiї, формування конфiгурацiї адсорбованих адатомiв описано як перехiд першого роду. Критична температура зонда лiнiйно зростає з ростом
ефективного значення модуля зсуву зразка i зменшується при зростаннi його характерного значення.